Fundamentos da política no mundo secularizado, segundo Hannah Arendt - Souza, Roberto Lopes de (2013)
This research analyzes the way Hannah Arendt thinks the politics in the secularized world. We start from her criticism about the tradition of the Western Political Philosophy, characterized by the submission of the politics to the immutable truths, contemplated by philosophers. This concept was initiated by Plato and continued through the alliance between Church and Empire, extending to the beginning of the Modern Age. Philosophers like Hegel, Kierkegaard, Marx and Nietzsche, wanted to break with this tradition, but they could not do that on a satisfactory way. According to Arendt, the exchange of traditional patterns by others happened in the twentieth century, specifically in the deployment of totalitarian regimes, like the Nazism and the Bolshevism. Thus, the issue is to determine if it is possible to overcome the tendency to totalitarianism in the politics without resorting to transcendent categories offered by philosophy and religion. Our position is that Arendt defends the secularization, but does not consider enough the break with the transcendent reference. There are other positions that need to be observed for the policy happens, especially the exchange of views, based on the respect for human plurality. Besides the independence between politics and religion, we believe that her political theory propose a new relationship between politics and philosophy. After considering the overcoming of the metaphysics in politics, and the consequent hierarchy elimination between contemplation and action, we analyze the way the author presents the relationship between the speech and appearance. We realize that the political action requires a defined space, in which citizens can make pacts with each other. The durability of a common world depends on overcoming the subjectivism, characteristic of the modern times liberalism, in which predominates the private freedom. Similarly as in the revolutions of the eighteenth century, the difficulty of the politics in the modern world is to balance stability and novelty. Arendt offers the promise to ensure continuity, and the forgiveness to break the causal chain of the events and provide a new start. In politics, the novelty is possible when the action is linked to thought, but not the speculative thought, which aims to make universalization. That s why, for Arendt the policy does not require a rational system of predefined truths, but this does not mean that she is opposed to any kind of encounter between philosophy and politics, but the traditional model. She accepts the proposal of Socrates, in which the activity of thinking is more important than the result of thought. There she meets a limit to evil and allows us to start thinking about the relationship between ethic and politics. However, the Socratic principle is also limited, revealing what not to do, but not helping to establish a new action. Then, Arendt analyzes the Kantian philosophy, and despite rejecting the requirement of the will concept, she accepts the notion of judgment faculty, considering that this is the faculty that allows us to make policy.